Presencia de la raya águila de piel áspera Aetomylaeus asperrimus (Chondrichthyes: Myliobatidae) en la costa del Pacífico Norte de Costa Rica - Chávez, Elpis J.; Heidemeyer, Maike; Arauz, Randall; Arauz-Naranjo, Daniel; Mora-Vargas, Randall; Molina-Quirós, José Luis; Hernández-Muñoz, Sebastián (Revista Ciencias Marinas y Costeras, 2022)
Almost 25% of skates and rays’ information worldwide is insufficient to assess their extinction risk. We reported the first seven confirmed records of the rough eagle ray (Aetomylaeus asperrimus) along the north Pacific coast of Costa Rica. These findings suggest that encounters with this species are rare, possibly associated with oceanographic patterns. More information is needed to make accurate assumptions on the species’ abundance, ecology, and conservation needs.